The unobtrusive knowledge test: validity and stereotype threats - Martin, Daniel E; Moore, Carol F; Hedgspeth, Carol (Equal Opportunities International, 2009)
Purpose - The purpose of this paper is to validate the unobtrusive knowledge test (UKT) in a minority population, and examine its potential for limiting stereotype threat.Design methodology approach - Study One: (convergent validity): UKT and Wonderlic Personnel Test (WPT) scores were correlated for 131 students. Study Two: (stereotype threat) 202 minority students were placed into one of four groups based on whether or not they were given instructions to elicit stereotype threat, and whether they took the Excellence scale of the UKT or the WPT.Findings - Correlations provided evidence of convergent validity between the Excellence subscale of the UKT and the WPT. The stereotype threat study was inconclusive, with no differences being seen in the threat non-threat conditions for the WPT, and higher scores in the threat condition than the non-threat condition for the UKT.Research limitations implications - Unreliability of some scales and low correlations of others with the WPT, lessened the overall UKT's convergent validity.Practical implications - The need to develop measures of intelligence not subject to adverse impact is clear, and the results of the current research provide justification for further research establishing the properties of the UKT as a selection tool.Originality value - This paper offers new evidence of the usefulness of the UKT as a measure of cognitive ability for minority populations, and raises questions about the impact of stereotype threat on the UKT test.